(3JPcQI Chdj GdCdHGH hGdLGeY ddYLH GdYLGHs - (3OGhO Hf YeQ GdHUjQ GdCfWGcj, J (B1008 (3g` s ((3eMeO Hf eMeO Hf SYjO GdTQjaj GdgTJhcj s)
(3ChdgG (B:s
(3MQa GdPGd GdeYLeI(B: (3PGafHOGS, jSei HGdeZQHj eGPQjhf fHGJ YQV GdChQGb CHjV GdRgQ s
(3BNQgG (B:s
(3agPG LeGY eG JOYh GdMGLI Edjg ef gPg GdUfGYI, heG YOGg aJWhjd HdG aGFOI hGddg SHMGfg hJYGdi CYde s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B165s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B48 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(1363 (3O(B/1) s
Keywords: (3GdWHs